(untitled) (Research, Society and Development, 2022)
Objective: to analyze the quality of filling in the CSC in the childcare consultation at the PHC, aiming at promoting healthy child development. Methodology: this is a cross-sectional field research, with a descriptive objective and quantitative approach. Data collection was carried out by analyzing the Handbooks of children aged 0 to 2 years who attended the Family Health Strategies in the municipality of Pedro II- Piauí. Results: the results show that the fields that obtained the highest frequency of filling were related to the data to be filled in by the children’s guardians, with a percentage of 97.5%. Of the items to be registered in the maternity wards, birth weight and head circumference showed a higher proportion of filling, both with a percentage of 87.5% and of those to be registered in Primary Health Care, the vaccine fields were the most filled with 98.75%. The fields referring to neuropsychomotor development and oral health were not filled in almost all the passbooks. Conclusion: However, the results obtained with the study showed a low frequency of records, especially those to be filled out in health services.